Notarial KYC Principle and Legal Uncertainty in Foreign Capital Company Formation - Muhamad Fajar Ramadhan; Djumikasih Djumikasih; Dyah Widhiawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The increasingly globalized investment climate has made Indonesia a strategic destination for Foreign Direct Investment (FDI), particularly through the establishment of Foreign Investment Limited Liability Companies (PT PMA). However, the regulatory framework surrounding the Know Your Customer (KYC) principle—locally known as Prinsip Mengenali Pengguna Jasa (PMPJ)—implemented by notaries in this process remains incomplete. This creates legal uncertainty and potential risks for both notaries and foreign investors, especially in the context of anti-money laundering enforcement. This study addresses two main problems: the impact of regulatory incompleteness regarding PMPJ on foreign investors in the PT PMA establishment process, and how PMPJ should be regulated for notaries dealing with foreign investment. The research uses normative juridical methods with a statute and conceptual approach, relying on primary, secondary, and tertiary legal materials and analyzed using grammatical and systematic interpretation. The findings reveal that existing regulations, including the Minister of Law and Human Rights Regulation No. 9 of 2017, do not adequately specify the verification and transaction monitoring procedures for foreign users of notarial services. This regulatory gap results in procedural confusion, potential legal liability for notaries, and hampers the state's efforts to combat transnational financial crimes. The study recommends the formulation of clearer and integrated PMPJ regulations, the development of digital verification systems, and enhanced institutional coordination to ensure legal certainty and protection for all stakeholders involved.